HbA1c as a Predictor of Postoperative Infection in Type 2 Diabetic Patients after Coronary Artery Bypass Grafting (Global Journal of Medical Research, 2020)
Coronary artery disease (CAD) is one of the leading causes of morbimortality worldwide. In patients with diabetes mellitus type 2 (DM2), CAD is more likely to be a complex disease and often requires cardiac surgery. Furthermore, perioperative blood glucose levels control is associated with the followingoutcomes: surgery success, mortality, and infection postoperative. This is a retrospective study, we have collected data form, 43 patients, between 2015 and 2017, with diabetes type 2 and who had passed through a Coronary Artery Bypass Grafting. Those with infection postoperative had a glycohemoglobin 7, 9 (SD ±1,4), and those without infection had an HbA1c 7, 25 (SD ±0,94) and a p-value from 0,039. Adding this was identified that the average of creatinine clearance in patients with the infectious disease was 59 (SD ±21, 3) and 67 (SD ±26) in those without infection, calculated a p-value from 0,039. High levels of Hb1Ac are a predictor of infection disease postoperative.
Keywords: diabetes mellitus; coronary disease; cardiovascular surgical procedures; cross infection; glycated hemoglobin A